You Can't Be Serious! - Cotter, Jim (Theology & sexuality, 2000)
Jim Cotter frames this paper in the form of a one-sided conversation with Michael Vasey about two particular phrases that Vasey was responsible for in the current Anglican liturgy. The first comes from the baptismal rite and talks of the candidate submitting themselves to Christ as Lord. By reference to marriage and other liturgical contexts, Cotter asks whether this is an appropriate image for the twenty-first century, especially in the light of the debate about sexual abuse. The second phrase is taken from the Easter liturgy and talks of light invading the darkness. Once again Cotter challenges the military implications of this language and the negative associations that such a phrase gives to ‘darkness’ Cotter makes a call for far more careful reflection on the use of language in worship and offers a number of alternative suggestions of his own.